Stressed systems: Stroke unit bed occupancy and impact on reperfusion therapy in acute ischemic stroke - Blauenfeldt, Rolf A.; Damgaard, Dorte; Simonsen, Claus Z. (Frontiers in Neurology, 2023)
Objectives: We observed a decrease in the number of patients offered reperfusion therapy. We aimed to investigate if hospital system pressure measured as percentage of stroke bed occupancy influenced decisions on treatment and disposition. Design: Data from a regional quality of stroke care database was obtained and linked it to organisational data monitoring the hourly inpatient stroke bed occupancy rate. Logistic regression was used to analyse the relationship. Results: A total of 15,025 admissions were included from January 1, 2019 to August 24, 2022. Of these, 5,659 (38%) had acute ischemic stroke. The rates of reperfusion therapy treatment were highest in 2019 (36.2%) and 2020 (34.1%) and declined afterwards (30.0% in 2021). In the logistic regression analysis, occupancy rate ≥ 85% in the hour of the first admission was associated with reduced odds of admission at the stroke unit within 3 hours from symptom onset (adjusted odds ratio: 0.80, 95% confidence interval: [0.71-0.90], p<0.001) and a reduced odds of receiving reperfusion therapy (adjusted odds ratio: 0.83 [0.73-0.95], p=0.007) Conclusions: Increased bed occupancy level in the hour of first hospital admission for stroke patients was strongly associated with decreased odds of receiving reperfusion therapy.